OPPOSITIONAL DEFIANT DISORDER AND ITS MANAGEMENT STRATEGIES AMONG GENERAL AND SPECIAL EDUCATION TEACHERS - Alhowiml, Moody Saud; Alothman, Ibrahim Abdullah (PEOPLE: International Journal of Social Sciences, 2018)
The current study aimed to identify knowledge of Oppositional Defiant Disorder (ODD) definition, and its management strategies among general and special education teachers of primary school as a main objective, while there were other goals about the effects of job, experience, and level of education on their knowledge of ODD definition, and its management strategies. The study adopted descriptive approach, and design a questionnaire depends on the goals and questions of this study. Moreover, the researcher administrated on (699) female of general and special education teachers. The findings of the study were the level of knowledge of ODD management strategies is high, but the level of knowledge of ODD definition is moderate. The study found statistically significant difference at the level of (0.01) among the average of teacher’s responses according to job variable for special education teachers on the total score of the knowledge of ODD definition. Also, there was significant difference at the level of (0.01) among the average of teacher responses according to experience variable for teachers who have had experience between 5 to 10 years on the total score of the knowledge of ODD definition. However, there were no significant differences among the average of teacher’s responses according to the level of education. Training courses and workshops for general education teachers, and some topics for future researches were suggested such as the extent of correlation between ODD and disabilities of special education students.